Granulomatous Hepatitis Following Intra-Vesical Instillation of Bacillus Calmette-Guérin for Treatment of Bladder Cancer - Elsa Alves Branco; Raquel Duro; Teresa Brito; António Sarmento (MDPI AG, 2021)
Intra-vesical instillation of bacillus Calmette-Guérin (BCG) is an important treatment modality of superficial bladder cancer. It is usually well tolerated, although some adverse reactions can occur. One possible yet rare complication is granulomatous hepatitis, that is thought to be caused either by BCG infection or a hypersensitivity reaction to the bacillus. We present a case of a 79-year-old apparently immunocompetent patient who developed granulomatous hepatitis a few months after BCG administration for bladder cancer immunotherapy. It is important to notice that acid-fast smears and cultures are often negative, and these should not exclude diagnosis nor delay treatment. Our case highlights the importance of clinical suspicion and prompt initiation of appropriate treatment.